Degree of Phonological Contrast in Contemporary Persian Language - Mahmood Bejankhan; Sedigheh Roshan Ghanbari (نشریه پژوهش‌های زبان‌شناسی, 2020)
Abstract In this article, the current Persian phonological contrast system is addressed under the framework of functionalism. The Degree of Phonological Contrast (DC), as a quantitative index, is determined for consonants in terms of sonority, manner, and place of articulation, and tongue height, place, and length for vowels. The findings of this study demonstrate that DC can be explained for consonants and vowels in similar and dissimilar phonological classes. Keywords: minimal pairs, degree of contrast, functional load, sonority, phonological class   Introduction The main question in this article concerns the extent to which Persian phonology employs the contrast of a pair of phonemes in the word formation. This question is already reported for consonants and vowels. The hypothesis of the research implies that decreasing the similarity of the opposition members in phonological features increases the prevalence of minimal pairs and vice versa. For this purpose, the phonological contrast and functional load of the functionalism are quantified according to the formula of the DC. Then, the DC mean is determined for consonants in terms of initial, middle, and final positions within words, and the number of syllables for vowels using non-linear mathematical functions. Findings confirmed that the dissimilarity of vowels in length, along with the similarity of consonants in non-sonority and coronality, are among the pervasive factors in Persian word formation.   Materials and Methods Research data include 41718 minimal pairs extracted from the generative lexicon(Eslami et al., 1383) with a volume of 52858 entries using a computer program. In this program, each entry’s phonological form is compared with phonological forms of approximately the same length (with one unit of length error). If the difference is one, the two words are considered a minimal pair. Minimal pairs that differed in consonants were classified according to their beginning, middle, and end. Moreover, those that differed in vowels were classified according to the number of syllables. Diagrams of exponential and logistic functions were employed to study the relationship between the DC in consonants and the position of consonants at the beginning, middle, and end of words on the one hand, along with the relationship between the DC of vowels and the number of syllables on the other. To evaluate the research hypothesis, a comparison between the values ​​of DCs, as well as their descending order, was performed.   Discussion and Conclusion Examining the minimal pairs in the Persian lexicon shows that the DC of Persian consonants increases as we move from the beginning to the end of the word. Moreover, as the number of syllables increases, the DC of vowels decreases, and the inflection point of DC mean variations rest on three-syllable words. Conversely, as the number of syllables increases, the DC of consonants decreases, while there is no inflection point of DC mean variations on three-syllable words. Overall, DC for dissimilar classes is greater than that of similar classes. Specifically, the DC of vowels (in terms of tongue height and length) for dissimilar classes is more than that of similar classes, while it is the opposite for the place of articulation. However, the DC of consonants varies according to sonority, manner, and place of articulation for both similar and dissimilar classes. Therefore, the members of minimal pairs tend to be non-sonorant and coronal.